The Empowerment of the Cultural Dimension and Work Competence Among Technical Students - Saleh, Nor Shela; Siti Khairizah Mohmed,; Khairunesa Isa, (Human Sustainability Procedia, 2023)
Employment patterns are evolving, necessitating comprehensive qualifications. Insufficient competence and limitations in competence restrict employment opportunities, particularly for "fresh graduates." Given that the demand for work surpasses the quantity available, this competition and restrictions raise Malaysia's jobless rate. Due to the smaller job opportunities readily accessible, employers are more demanding in terms of conditions for employees. Graduates are competitive in the job market due to the different perspectives on cultural dimensions such as gender, sort of work, philosophical path, and job possibility. Knowledge proficiency and competency empowerment should be prioritised in the refinement work requirements for the IR 4.0 revolution. All graduates need to acquire holistic competencies to be ready to engage in both conventional and virtual employment. Intrapersonal skills, planning skills, problem-solving skills, communication skills, logical thinking skills, teamwork skills, proactive attitude skills, and technology skills are a few of the merged competencies that graduates should master. Empowerment in multiple abilities is critical to guaranteeing that it will become a pioneer for graduate employability in the future.